Upstaged from cT1a-c to pT2a lung cancer, related to visceral pleural invasion patients, after segmentectomy: Is it an indication to complete resection to lobectomy - ÖZGÜR, EMRAH GÖKAY (My University, 2023)
Segmentectomy may be indicated for T1a-cN0 non-small cell lung cancer. However, several patients are upstaged pT2a at final pathological examination due to visceral pleural invasion. As resection is usually not completed to lobectomy, this may raise issue of potential worse prognosis. The aim of this study is to compare prognosis of visceral pleural invasion upstaged cT1N0 patients operated on by segmentectomy or lobectomy.
Keywords: Segmentectomy; Visceral pleural invasion; Early-stage lung cancer